2020
DOI: 10.1002/jctb.6376
|View full text |Cite
|
Sign up to set email alerts
|

A green approach for treatment of wastewater with manganese using wood ash

Abstract: BACKGROUND: In the circular economy context, the present article proposes a green technical solution by manganese ions adsorption on oak wood ash and the reuse of the new waste generated by the adsorption process as soil amendment. RESULTS:The influence of the main process variables: pH, adsorbent dose and contact time was investigated for optimal manganese ions adsorption. The highest adsorption efficiency of the wood ash (more than 98%) was recorded at pH 6, adsorbent dose of 10 g L −1 and contact time 15 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Similar results for different metal ions were obtained by other researchers when using wood ash. In a study by Mosoarca et al [ 37 ], ash obtained from wood-burning was used to retain Mn 2+ ions from wastewater. They found that the material presents an adsorption efficiency of over 90% but can be increased to over 98% by parameter control, with best values obtained for pH~6, a material dose of 10 g/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results for different metal ions were obtained by other researchers when using wood ash. In a study by Mosoarca et al [ 37 ], ash obtained from wood-burning was used to retain Mn 2+ ions from wastewater. They found that the material presents an adsorption efficiency of over 90% but can be increased to over 98% by parameter control, with best values obtained for pH~6, a material dose of 10 g/L.…”
Section: Resultsmentioning
confidence: 99%
“…Ash obtained from different waste biomass has been also recognized as an adsorbent for metal removal from polluted waters. Ash obtained from wood-burning has proved to be efficient for the removal of Mn 2+ ions from wastewater [ 37 ], Cr 4+ ions [ 38 ]. Borlodoi et al studied how ash obtained from banana peels can remove iron ions from groundwater from a concentration of 20 mg/L to 0.3 mg/L [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbent dose has a greater influence on process efficiency due to the adsorption surface area and the number of sites available for adsorption increase with the adsorbent material dose [ 14 , 36 , 49 ]. Another parameter that has a great influence on the process is pH.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table S3, temperature had a less crucial contribution to SMT adsorption. High temperatures usually reduce the solution viscosity and thus provoke the mobility of the SMT cations [58].…”
Section: Thermal Properties Of the γ-Fe 2 O 3 /Mwcnt/ag Nc Particlesmentioning
confidence: 99%